THE GROSS AND MICROSCOPIC ANATOMY OF THE CAROTID BODY OF AN ENDOGENOUS DUCK - S. Mohammad, F.; S. AL-Samarrae , N.; O. Rabie, F. (The Iraqi Journal of Veterinary Medicine, 1996)
The carotid body in an endogenous duck was closely related to the ventral surface of the common carotid bifurcation zone caudal to the parathyroid glands. The carotid body was characterized by its compact and fusiform shape. Taking into account all carotid bodies, the mean length was 1.058 +0.95 micrometers. The blood supply of the carotid body in duck was not detected easily but caudal and cranial thyroid arteries gave many branches to it. Histologically, the carotid body of an endogenous duck was consisted of two types of cells; chief cells which occurred in groups and were invested by sustentacular cells. These cells were embedded within a connective tissue fibers to form glomic tissue. A collection of ganglionic cells were observed in the vicinity of the carotid body